Dynamics of changes in the level of propensity to use the Internet in European Union countries in 2010-2019 - Oesterreich, Maciej (Dynamika zmian poziomu skłonnosci do wykorzystania Internetu w państwach Unii Europejskiej w latach 2010-2019, 2019)
The article analyses the level of propensity to use the Internet in 28 countries of the European Union in 2010 and 2019 and assesses its dynamics of changes in this period. For this purpose, information available in the databases of Eurostat and the World Bank regarding the ways in which the Internet was used by citizens and households. The study omitted issues related to the commercial use of the Internet potential by enterprises. For individual years, taxonomic synthetic measures were constructed based on a set of diagnostic features, using the TOPSIS method. These measures determine, respectively: the level of willingness to use the network by citizens and households of individual EU countries as well as the rate of changes in the analysed period. The research shows that the highest propensity to use the Internet was characteristic of citizens of Northern European countries and the lowest was in Southern Europe. The R environment and the Statistica package were used for the calculations
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 7, s. 102-117
Keywords: use of the internet; European Union countries; level of propensity; wykorzystanie internetu; kraje Unii Europejskiej; poziom skłonności